PELATIHAN BAHASA INGGRIS PERBANKAN DAN KEUANGAN PADA KARYAWAN BNI 46 DI CENDIKIA COURSE - Hera Hartati; Herysa Oktawati; Anggia Pratiwi (AbdiMasya | Hira Institute, 2026)
This community service aims to improve the English skills of BNI 46 Bangko branch employees, especially English for specific purposes, namely banking and finance, through training. This training is motivated by the rules of the BNI head office in upgrading employees' English language skills and to support administrative work and speaking skills that require them to deal with English-language documents and interact with customers from abroad who come to Merangin. The training involves partners, namely the Cendikia Course Institute. This training is carried out for 2 months in the form of learning carried out both online and offline. The training participants numbered 20 people who were divided into two study groups held on weekends for offline meetings, and assignments in the form of modules or worksheets for online meetings. and at the end of the training, participants took a proficiency test related to the learning they had taken and would receive a certificate of proficiency. The results of the training showed an increase in motivation and ability of participants in English banking and finance, especially an increase in vocabulary, writing, speaking, listening and reading skills).